"KONSENSUM” TUSHUNCHASINING O’ZLASHTIRISHI YUZASIDAN OLIB BORILGAN TADQIQOT VA UNING NATIJALARI - Qodirova Munisabonu Ibrohimjon qizi (TADQIQOTLAR, 2025)
Abstract: This article presents the research conducted on the assimilation of the concept consensus into the Uzbek language and discusses its key findings. The study examines the linguistic, semantic, and cultural aspects of the concept, identifies its Uzbek equivalents, and analyzes its functional features and usage contexts in Uzbek discourse. Surveys conducted among respondents helped determine the perception, comprehension, and frequency of use of the concept “consensus” in the Uzbek language. The findings contribute to developing recommendations for the effective integration of this concept into Uzbek and its appropriate use in both scientific and social discourse.